STRATEGI PEMASARAN MOTOR HONDA PADA PT. BINTANG MOTOR BENGKULU - Andriyani Prawitasari; Englin Roziz (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This study aims to determine the marketing strategy of PT. Bintang Motor Bengkulu. The analysis method was used SWOT analysis consist of Internal Strategy Factor Matrix (IFAS) and External Strategy Factor (EFAS).SWOT analysis results obtained from the strength value is 25.71 while the weakness is 13.26 so the internal quadrant factor is 25.71-13.26 = 12.45, it means the ability of PT. Bintang Motor Bengkulu in harnessing the strength and minimize the weaknesses that are in the internal company. Opportunities of the strategy is 19.30 and the threat of 12.52. So the external quadrant factor is 19.30 - 12.52 = 6.78 means the high ability of of PT. Bintang Motor Bengkulu in exploiting the opportunities and overcome the threats faced by the company in the sale. So that is in the first quadrant is an aggressive strategy by applying: 1) Maintaining the quality and quality of honda products and perform services that can believe and satisfy consumers. 2) Harness the power in marketing the product based on quality and quality through promotion, sponsorship and exhibition so that of PT. Bintang Motor Bengkuluare increasingly believed and known to the public.